2017
DOI: 10.21276/apalm.2017.1143
|View full text |Cite
|
Sign up to set email alerts
|

Is HPV virus associated with human breast cancer? Time to re-examine the postulate. Egyptian Study

Abstract: Background: There is increasing evidence that high-risk human papilloma virus (HPV) is involved in cancers in addition to cervical cancer. Infectious agents are thought to be responsible for approximately 16% of cancers worldwide, however there are mixed reports in the literature regarding the prevalence and potential pathogenicity of viruses in breast cancer. Methods:We screened 30 fresh frozen breast cancer tissue specimens collected immediately postoperative from patients in Ain-Shams University Hospital fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Sample size calculation: the total number of cases that attended NCI with BC was estimated to be 2500 per year. A previous study conducted in Egypt by El-Sheshtawy et al (2017) 31 indicated that the overall prevalence of HPV in malignant breast tissue was 16.7%. For a two-sided 95% confidence interval for a single proportion based on these criteria, the minimum required sample size to evaluate the practice was 54 cases with a 10% margin of error.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Sample size calculation: the total number of cases that attended NCI with BC was estimated to be 2500 per year. A previous study conducted in Egypt by El-Sheshtawy et al (2017) 31 indicated that the overall prevalence of HPV in malignant breast tissue was 16.7%. For a two-sided 95% confidence interval for a single proportion based on these criteria, the minimum required sample size to evaluate the practice was 54 cases with a 10% margin of error.…”
Section: Methodsmentioning
confidence: 93%
“… 39 Another report from Egypt demonstrated the presence of HPV DNA in 16.7% of fresh BC tissues. 31 Other studies demonstrated the absence of HPV DNA in fresh tissues. 40 The difference in result may be due to low viral load, 41 , 42 possible inter-laboratory inconsistency in collecting and handling samples 38 and storage of specimens.…”
Section: Discussionmentioning
confidence: 98%
“…12 The frequency of infection with HR-HPV genotypes in Egyptian women with BC was reported (22.2%) and is consistent with previously published worldwide data. 12,28,[55][56][57][58][59][60][61][62][63] The lower HR-HPV detection rate reported in some studies may be a result of difficulties in PCR detection due to low viral load in BC in different populations. [64][65][66] We detected HR-HPV in cancerous tissue or noncancerous safety margin adjacent to BC tissue as previously reported.…”
Section: Discussionmentioning
confidence: 99%